Nuzi texts and their uses as historical evidence - Maidman, M. P. (Writings from the ancient world ;, 2010)
Ancient Nuzi, buried beneath modern Yorghan Tepe in northern Iraq, is a Late Bronze Age town belonging to the kingdom of Arrapḫa that has yielded between 6,500 and 7,000 legal, economic and administrative tablets, all belonging to a period of some five generations (ca. 1475-1350 B.C.E.) and almost all from known archaeological contexts. The ninety-six Akkadian texts presented here in transliteration and translation are divided in five groups dealing with topics of historical interest: Nuzi and the political force responsible for its demise; the crimes and trials of a mayor of Nuzi; a multigenerational legal struggle over title to a substantial amount of land; the progressive enrichment of one family at the expense of another through a series of real estate transactions, and the nature of the ilku, a real estate tax whose dynamic is crucial in defining the economic and social structure of Nuzi as a whole.